PENGARUH MOTIVASI BELAJAR DAN PENDAPATAN ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IISDI SMA NEGERI 1 PANGKALAN LESUNG - Sofi Alfia Mairanti; Suarman Suarman; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of learning motivation and parents' income on student learning outcomes, both partially and simultaneously in Economics Class XI IIS at SMA Negeri 1 Pangkalan Lesung. The subjects of this study were 70 students of class XI IIS at SMA Negeri 1 Pangkalan Lesung, the sample taken in this study using saturated samples. The data used are primary data and secondary data with data collection techniques using a questionnaire / questionnaire and documentation. The data analysis technique used is Multiple Linear Regression Analysis. The results showed that learning motivation and parents' income had a significant effect simultaneously on learning outcomes in economics subjects for class XI IIS students at SMA Negeri 1 Pangkalan Lesung. This means that high learning motivation and parents' income will lead to high student learning outcomes in economic subjects and vice versa if learning motivation and low parental income will trigger low student learning outcomes in economic subjects in class XI IIS students at SMA Negeri Pangkalan Lesung. To improve student learning outcomes, teachers can help by developing and applying their creativity so that students have high creativity and improved learning outcomes, and students must also make the best use of the creativity provided by the teacher, including in class management and developing learning media, thus learning in the classroom will be fun and the learning outcomes will be high. Key Words: Learning Motivation, Parents' Income, Learning Outcomes